The undrained shear strength of soft clay reinforced with group encapsulated lime bottom ash columns - Wong, Suk Chee (2017)
Environmental issues due to the storing coal ash in ash ponds has come to a serious stage and endanger human’s health, and this cause human to realize the importance of utilization coal ash. Utilizing bottom ash column as granular column, this is an alternative method to replace granular with coal burnt by-product so that it is balance between economic growth and environmental. Quicklime was used to mixed with bottom ash to increase the bonding between bottom ash particles. Thus, it helped in improving the strength of coal ash in term of shear strength and bearing capacity. Apart from that, quicklime also helped in stabilize soft clay soils, as diffusing of lime from lime bottom ash column can be happened after some time. This research was aimed to investigate the role of group encapsulated lime bottom ash columns in improving the shear strength by using laboratory scale model. Kaolin was being used as soil sample and lime bottom ash as the reinforced columns. The reinforced kaolin samples were tested by using Unconfined Compression Test (UCT). Moreover, few laboratory experiments were conducted to know the physical and mechanical properties of bottom ash, kaolin clay, and quicklime sample. A total 7 batches of kaolin sample had been tested and each batch consist of 3 specimens represent sample without lime bottom ash column, partially penetration and fully penetration for group lime bottom ash columns. The specimen used were 50 mm in diameter and 100 mm in height. The diameters of group lime bottom ash columns were 10 mm and 16 mm. The height of the group columns were 60 mm, 80 mm and 100 mm. The group encapsulated lime bottom ash columns was installed in triangular pattern, as it was much easier to maintain the location of installed columns and the spacing in between the columns. The improvement of shear strength of group encapsulated lime bottom ash columns with area replacement ratio of 12.00 % (10 mm column diameter) and 30.72 % (16 mm column diameter) was 29.00 %, 44.17 %, 29.75 % and 1.00 %, 3.92 %, 7.33 % at sample penetration ratio, Hc/Hs of 0.6, 0.8 and 1.0 respectively. It can be concluded that the shear strength of soft clay could be improved by installation of group encapsulated lime bottom ash columns. However, the improvement of shear strength of 10 mm group encapsulated lime bottom ash columns was increased more significant compared to 16 mm group encapsulated lime bottom ash columns.